A case report of neurofibromatosis - Shimae Nafarzadeh; Mina Motallebnejad; Anahita Ghorbani; Naghmeh Jamaatlou (Babol University of Medical Sciences, 2014)
Introduction:Neurofibromatosis is a genetic disease characterized by multifocal benign tumors of peripheral nerves, called neurofibromas, and pigmented spots on the skin which inherited as autosomal-dominant. The most common form of the disease is neurofibromatosis type 1, also known as von Recklinghausen's disease of the skin. When an individual has small number of lesions in a limited region of the his body, it could be missed by the patient or not acknowledged by the clinicians as a form of neurofibromatosis. We present here, a case of an 18-year-old male with neurofibromatosis type 1who referred to Babol Dental School for a routine dental examination.